2014
DOI: 10.1515/jpem-2013-0246
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of risk of deficiency and inadequacy of 25-hydroxyvitamin D in US children: NHANES 2003–2006

Abstract: Approximately 10.3% of US children aged 6-18 years (population estimate 5.5 million) have 25(OH)D levels <16 ng/mL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 11 publications
3
17
0
Order By: Relevance
“…3638 The 40% prevalence of low 25(OH)D in our cohort was similar to those of cohorts of healthy children in the northeastern US 37 and PHIV children in New York City. 7 Our prevalence of vitamin D deficiency was higher than the 24% observed in 6–18 year-old children in the NHANES representative US sample of this age group, 38 but lower than the ≥50% reported in behaviorally HIV-infected adolescents. 12,13 Differences across studies are likely attributable to age, race, prevalence of obesity, latitude, sun exposure, season of sampling, and dietary intake.…”
Section: Discussionsupporting
confidence: 75%
“…3638 The 40% prevalence of low 25(OH)D in our cohort was similar to those of cohorts of healthy children in the northeastern US 37 and PHIV children in New York City. 7 Our prevalence of vitamin D deficiency was higher than the 24% observed in 6–18 year-old children in the NHANES representative US sample of this age group, 38 but lower than the ≥50% reported in behaviorally HIV-infected adolescents. 12,13 Differences across studies are likely attributable to age, race, prevalence of obesity, latitude, sun exposure, season of sampling, and dietary intake.…”
Section: Discussionsupporting
confidence: 75%
“…It has been long known that vitamin D deficiency causes rickets in children and osteomalacia in adults (2). Among healthy children and adolescents in the United States, the prevalence of deficiency is 9-18% (3)(4)(5).…”
mentioning
confidence: 99%
“…The survey found that 41.6% of participants were deficient (having 20 ng/ml or less of serum 25(OH)D). African Americans had the highest deficiency rate (82.1%) followed by Hispanics (69.2%) [30][31][32].…”
Section: Vitamin D Metabolism and Physiological Rolesmentioning
confidence: 99%